Relevansi Konsep Pendidikan Sosialis Perspektif H.O.S Tjokroaminoto dengan Pendidikan Agama Islam - Ainol; Ibrahim, Fuad (At- Ta'lim : Jurnal Pendidikan, 2020)
This article is motivated by the writer's admiration for the pearl of HOS Tjokroaminoto's thoughts in the field of education. The concept of education that he initiated during the pre-independence era was almost unreadable by the present generation, even though the sparkle of his thought in education was still relevant, actualized in the current era, especially among Muslims. Non-discriminatory education that distinguishes social classes, poor and rich, the nobility and the proletariat is strongly opposed and opposed. This kind of education is now appearing in a new form of superior schools, model schools that in practice only bear cubs can enter it, while poor people cannot go to school. On the basis of these problems, this paper will answer a) what is the concept of Tjokroaminoto's version of socialist education? b) how relevant is it to Islamic education? This study includes library research that focuses on texts that have to do with the problem under study. The results of this study, education must be populist, socialist, non-discriminatory, there is no dichotomy of religious knowledge and general knowledge and all knowledge must be based on monotheistic values.